2013
DOI: 10.1080/15438627.2013.825796
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Hyperhydration Versus Ad Libitum Fluid Intake Strategies on Measures of Oxidative Stress, Thermoregulation, and Performance

Abstract: Dehydration has been shown to augment cellular stress. Glycerol hyperhydration can delay dehydration, which may decrease the level of pre- and post-exercise oxidative stress. This study aimed to compare the effects of glycerol (G) or water (W) hyperhydration with no hyperhydration (C) on oxidative stress, thermoregulation, and cycle performance. Seven trained males consumed 1.2 g of glycerol·kg⁻¹ body mass (BM) in 26 ml·kg⁻¹ BM water or equal volume water to achieve hyperhydration followed by a 90 min time tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Hydration status was assessed via urine osmolality (UOsm) using a handheld digital refractometer (Osmocheck, Vitech Scientific Ltd, Horsham, UK) before any pre exercise measures were obtained and immediately after exercise. All participants were euhydrated [UOsm was <600 mOsmols.kg.H 2 0 (Hillman et al, 2011, 2013)] prior to all experimental conditions and remained euhydrated during each experimental trial despite UOsm increasing (Time; F = 63.7, p < 0.001) immediately post exercise compared to basal.…”
Section: Methodsmentioning
confidence: 99%
“…Hydration status was assessed via urine osmolality (UOsm) using a handheld digital refractometer (Osmocheck, Vitech Scientific Ltd, Horsham, UK) before any pre exercise measures were obtained and immediately after exercise. All participants were euhydrated [UOsm was <600 mOsmols.kg.H 2 0 (Hillman et al, 2011, 2013)] prior to all experimental conditions and remained euhydrated during each experimental trial despite UOsm increasing (Time; F = 63.7, p < 0.001) immediately post exercise compared to basal.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence was 100% in all participants. Participants were instructed to drink 500 ml of water 2 h before each experimental trial in line with the American College of Sports Medicine position stand (55) and recent work in the field (26,27). Hydration status was assessed via urine osmolality (UOsm).…”
Section: Experimental Designmentioning
confidence: 99%
“…Hence, the possibility that the beneficial effects of pre-exercise WIH on endurance performance were undermined in this study cannot be ruled out. In the study by Hillman et al (2013), completion time of a 90-km cycling time-trial was similar whether participants were subjected to pre-exercise WIH or euhydration. However, postexercise BW losses were ≤ 1% because participants drank sufficiently to counter BW losses, rendering pre-exercise hyperhydration of little practical use.…”
Section: Water-induced Hyperhydrationmentioning
confidence: 99%
“…To date, only three studies have investigated whether pre-exercise GIH benefits exercise performance compared to pre-exercise euhydration Hillman et al, 2013;Latzka et al, 1998). Both and Latzka et al (1998) have shown that preexercise GIH improved exercise time-to-exhaustion compared with pre-exercise euhydration.…”
Section: Glycerol-induced Hyperhydrationmentioning
confidence: 99%